2014
DOI: 10.3906/sag-1308-58
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary salt restriction on hypertension in peritoneal dialysis patients

Abstract: Background/aim: To investigate the effect of dietary salt restriction on blood pressure levels, total sodium removal, and hydration status of peritoneal dialysis (PD) patients.Materials and methods: Thirty-one stable PD patients who consulted a renal dietitian monthly for dietary recommendations, including restricted salt intake <5 g/day, and education about hypertension and hypervolemia were included in this study. Baseline and third month clinical and laboratory findings, bioelectrical impedance analysis res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
(30 reference statements)
1
7
0
Order By: Relevance
“…However, small studies have shown that restricting salt intake can reduce IDWG in patients receiving HD, 167 and BP in patients receiving PD. 168 Although the serum sodium level that triggers thirst varies across individuals, 169 most patients maintain their pre-dialysis sodium levels within the normal range. This finding suggests that water intake is adjusted to match salt intake, underscoring the importance of emphasizing salt restriction, rather than the overly simplistic advice to just restrict fluid intake.…”
Section: Salt and Fluid Restrictions For Bp And Volume Controlmentioning
confidence: 99%
“…However, small studies have shown that restricting salt intake can reduce IDWG in patients receiving HD, 167 and BP in patients receiving PD. 168 Although the serum sodium level that triggers thirst varies across individuals, 169 most patients maintain their pre-dialysis sodium levels within the normal range. This finding suggests that water intake is adjusted to match salt intake, underscoring the importance of emphasizing salt restriction, rather than the overly simplistic advice to just restrict fluid intake.…”
Section: Salt and Fluid Restrictions For Bp And Volume Controlmentioning
confidence: 99%
“…For haemodialysis patients, restricting sodium intake and increasing sodium removal by the use of lower dialysate sodium concentrations leads to an improvement in blood pressure control [19][20][21]. Similarly, both dietary sodium restriction and lower sodium dialysates been reported to lower blood pressure in peritoneal dialysis patients in the short term [13,22].…”
Section: Discussionmentioning
confidence: 99%
“…Most haemodialysis patients are oligo-anuric and there are potential errors in collecting and estimating dialysate sodium losses [12], we chose to study peritoneal dialysis patients as 24-hour urine and dialysate effluent collections are collected as part of routine clinical practice in the management of peritoneal dialysis patients. A previous study in peritoneal dialysis patients reported that a reduction in dietary sodium resulted in a reduction in total body water and blood pressure in normotensive patients [13], we wished to evaluate the usefulness of FFQs in clinical practice. We used 2 FFQs developed for use in the UK; the "Derby Salt Questionnaire" (DSQ) and the "Royal Free Salt Questionnaire (RFSQ) to estimate dietary sodium intake and to determine whether there was any association between DSQ and RFSQ scores and blood pressure, and the amount of extracellular water in peritoneal dialysis patients [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…61.2% participants had blood pressure above 160/100 mmHg with 19.9% patients who also had cardiac disease. İnal et al () demonstrated that even a small reduction in daily dietary salt intake can cause a significant decrease in blood pressure levels and fluid overload in patients undergoing peritoneal dialysis (İnal et al ).…”
Section: Discussionmentioning
confidence: 99%